EVALUASI PEMBELAJARAN PADA MATA PELAJARAN PENDIDIKAN JASMANI, OLAHRAGA DAN KESEHATAN (PJOK) SELAMA PANDEMI COVID-19 - Sutrisno (JURNAL EDUKASI: KAJIAN ILMU PENDIDIKAN, 2021)
This study aims to explore the implementation system of learning assessment in schools and the problems faced by teachers in Physical Education, Sports and Health (PJOK) subject during the Covid-19 pandemic. The type of research used was an exploratory qualitative which was conducted in a State Junior High School (SMP) in Surabaya. Sources of research data obtained from teachers PJOK as many as 40 respondents using questionnaire and interview. While the main instrument was the researcher who was prepared with a questionnaire and interview guidelines. The form of research data analysis was descriptive qualitative. The results showed that the implementation of the assessment of learning outcomes in schools during the Covid-19 pandemic was less effective and was not carried out optimally, especially in the cognitive, emotional and psychological aspects. Teachers could only use the WhatsApp application as the main means of the assessment process, some even use the Zoom Meeting, Google Meet or Microsoft Teams applications. It has been proven that the teachers only concluded from the work on the problem without validating the process. In addition, teachers faced obstacles in conducting this assessment, including: teachers were confused about which tools to use where the low technological skills of teachers, parents and students. Weak networks and high quotas were also obstacles in learning activities during the pandemic.